Youth Personal Decision Aid (YouthPDA): The preferred youth decision making areas - Ibrahim, Norfiza; Shiratuddin, Norshuhada; Sarif, Siti Mahfuzah (2013)
A study was conducted to identify the most applicable area for youth to utilize the Personal Decision Aid (PDA). There are eight areas of decision making namely study, career, lifestyle, purchasing, friendship, politic, religion and marriage have been explored in this study. An online survey gathered from 80 respondents, age 18 to 24 years old to participate in the study.The main objectives of the survey are to identify the preferred choice of aid in the mentioned areas as well as trying to figure out their intention to use the aid if provided.The outcome of this survey indicates that four main chosen areas from the youth are study, career, purchasing and lifestyle.